The Danish girl [videorecording (DVD)] - Redmayne, Eddie, 1982-; Vikander, Alicia, 1988-; Whishaw, Ben, 1980-; Ebershoff, David (Universal Studios Home Entertainment, 2016)
The remarkable love story inspired by the lives of artists Lili Elbe and Gerda Wegener. Lili and Gerda's marriage and work evolve as they navigate Lili's groundbreaking journey as a transgender pioneer.